Mitoxantrone loaded superparamagnetic nanoparticles for drug targeting: A versatile and sensitive method for quantification of drug enrichment in rabbit tissues using HPLC-UV - Tietze, Rainer; Schreiber, Eveline; Lyer, Stefan; Alexiou, Christoph (Journal of Biomedicine and Biotechnology, 2010)
In medicine, superparamagnetic nanoparticles bound to chemotherapeutics are currently investigated for their feasibility in local tumor therapy. After intraarterial application, these particles can be accumulated in the targeted area by an external magnetic field to increase the drug concentration in the region of interest (Magnetic-Drug-Targeting). We here present an analytical method (HPLC-UV), to detect pure or ferrofluid-bound mitoxantrone in a complex matrix even in trace amounts in order to perform biodistribution studies. Mitoxantrone could be extracted in high yields from different tissues. Recovery of mitoxantrone in liver tissue (5000ng/g) was 76 ± 2 . The limit of quantification of mitoxantrone standard was 10ng/mL ± 1 2 . Validation criteria such as linearity, precision, and stability were evaluated in ranges achieving the FDA requirements. As shown for pilot samples, biodistribution studies can easily be performed after application of pure or ferrofluid-bound mitoxantrone. Copyright © 2010 Rainer Tietze et al.
CRIS-Team Scopus Importer:2022-06-27